Teaching Spoken Narrative to Senior High School Students by Using Podcast - Herlina julia; Aryuliva Adnan (Universitas Negeri Padang, 2019)
This paper discuss about the use of Podcast in teaching spoken narrative. Podcast can be used by the teacher to improve the student’s motivation in learning narrative especially spoken narrative text. This media can be a solution for the teacher to solve the problem of teaching spoken narrative text. As known that the student in senior high school find some difficulties in learning narrative especially when they need to understand a too long material which is consist of some difficult words. Podcast consist of several material that can be a media for the teacher to teach spoken narrative easily. This media provide a various material including narrative to help the teacher to teach listening. Podcast can easily increase the student motivation because they can find a various material about narrative that can easily understood.